Radiation therapy affects YAP expression and intracellular localization by modulating lamin A/C levels in breast cancer - La Verde, Giuseppe; Artiola, Valeria; Pugliese, Mariagabriella; La Commara, Marco; Arrichiello, Cecilia; Muto, Paolo; Netti, Paolo A.; Fusco, Sabato; Panzetta, Valeria (Frontiers in Bioengineering and Biotechnology, 2022)
The microenvironment of breast cancer actively participates in tumorigenesis and cancer progression. The changes observed in the architecture of the extracellular matrix initiate an oncogene-mediated cell reprogramming, that leads to a massive triggering of YAP nuclear entry, and, therefore, to cancer cell proliferation, invasion and probably to increased radiation-resistance. However, it is not yet fully understood how radiotherapy regulates the expression and subcellular localization of YAP in breast cancer cells experiencing different microenvironmental stiffnesses. To elucidate the role of extracellular matrix stiffness and ionizing radiations on YAP regulation, we explored the behaviour of two different mammary cell lines, a normal epithelial cell line (MCF10A) and a highly aggressive and invasive adenocarcinoma cell line (MDA-MB-231) interacting with polyacrylamide substrates mimicking the mechanics of both normal and tumour tissues (∼1 and ∼13 kPa). We report that X-ray radiation affected in a significant way the levels of YAP expression, density, and localization in both cell lines. After 24 h, MCF10A and MDA-MB-231 increased the expression level of YAP in both nucleus and cytoplasm in a dose dependent manner and particularly on the stiffer substrates. After 72 h, MCF10A reduced mostly the YAP expression in the cytoplasm, whereas it remained high in the nucleus of cells on stiffer substrates. Tumour cells continued to exhibit higher levels of YAP expression, especially in the cytoplasmic compartment, as indicated by the reduction of nuclear/cytoplasmic ratio of total YAP. Then, we investigated the existence of a correlation between YAP localization and the expression of the nuclear envelope protein lamin A/C, considering its key role in modulating nuclear deformability and changes in YAP shuttling phenomena. As supposed, we found that the effects of radiation on YAP nucleus/cytoplasmic expression ratio, increasing in healthy cells and decreasing in tumour ones, were accompanied by lower and higher lamin A/C levels in MCF10A and MDA-MB-231 cells, respectively. These findings point to obtain a deeper knowledge of the role of the extracellular matrix and the effects of X-rays on YAP and lamin A/C expression that can be used in the design of doses and timing of radiation therapy.